Evaluation of hip joint laxity in crab-eating foxes (Cerdocyon thous) - Castilho, Maíra S. [UNESP]; Rahal, Sheila C. [UNESP]; Mamprim, Maria J. [UNESP]; Inamassu, Letícia R. [UNESP]; Dias Neto, Ramiro N. [UNESP]; Melchert, Alessandra [UNESP]; Matsubara, Lídia M. [UNESP]; Mesquita, Luciane R. [UNESP] (FapUNIFESP (SciELO), 2021)
Like canids, crab-eating foxes may probably be predisposed to similar orthopedic diseases of domestic dogs, such as hip dysplasia. However, for the adequate hip dysplasia diagnosis in wild animals, the normality characteristics of each species must be determined. This study aimed to estimate radiographic and computed tomographic (CT) values of hip joint laxity in healthy crab-eating foxes. Fifteen intact crab-eating foxes, eight males and seven females, ages 1 to 5 and mean body mass of 6.66kg were used. Norberg angle (NA) was calculated from ventrodorsal hip-extended radiographs. To calculate the dorsolateral subluxation (DLS) score, the center distance (CD) index, the lateral center edge angle (LCEA), and the dorsal acetabular rim angle (DARA), measurements obtained from transverse CT images were used. No statistically significant differences were observed between the right and left sides in the radiographic and tomographic parameters. The mean NA was 107.57°. The mean DLS score, the CD index, the LCEA, and the DARA were 60.79%, 0.16, 98.25° and 13.47°, respectively. The data obtained are helpful in characterizing mean values of the hip joint in healthy crab-eating foxes, and can contribute to the knowledge of the species.
Avaliação da lassitude da articulação coxofemoral em cachorro-do-mato (Cerdocyon thous)
Keywords: Cerdocyon thous; Computed tomography; Crab-eating foxes; Hip joint; Laxity; Radiography; Wildlife animals